BUILDING A QUALITY LEARNING ENVIRONMENT THROUGH CHRISTIAN RELIGIOUS EDUCATION IN THE 5.0 ERA - Juliana Loes; Yosep Heristyo Endro Baruno; Yosua Padama (CV. ADIBA AISHA AMIRA, 2025)
The Society 5.0 era demands significant changes in the education system, including in Christian Religious Education (PAK). The aim of this research is to explore the role of PAK in building a quality learning environment in the 5.0 era, where technology and spiritual values must go hand in hand. The research method used is a qualitative approach with literature studies and phenomenological analysis of the implementation of PAK in various educational institutions. The research results show that PAK has an important contribution in shaping students' character, improving digital ethics, and creating a holistic and inclusive learning environment. By integrating technology and Christian principles, education can be more adaptive to the challenges of the times without losing its spiritual essence. This study confirms that PAK plays a role as a foundation in building a generation that is not only intellectually intelligent, but also has high morality in the digital era.